Klippel-Feil Syndrome: morphological findings in a 19th-century musealized skull from Viana del Bollo (Orense, Spain) - Herrerín, Jesús; Dorado, Enrique; Galassi, Francesco M.; Varotto, Elena; Solà, Rosa Dinarès (Anthropological Review, 2022)
The aim of this study is to show the cranial alterations that Klippel-Feil syndrome produced in a case older than 200 years. Few paleopathological case studies diagnosed as Klippel-Feil Syndrome are focused on cranial abnormalities. A skull numbered 778, belonging to the Federico Olóriz Aguilera collection (Spain, 19th century AD), Universidad Complutense de Madrid, belonging to a young man born in a town in the North of Spain, was investigated. This cranium was visually inspected, hence macroscopically and paleoradiologically studied, using the images obtained through conventional radiology and CT scan imaging. In addition to the vertebral fusion between the atlas (C1) and the axis (C2), atlanto-occipital fusion, basilar impression, obliteration of the sagittal suture, enlarged parietal foramina and significant craniofacial asymmetry affecting maxillary bones, sphenoid, orbits, nasal bones and both palatines were observed. Morphological findings make it possible to diagnose a Klippel-Feil syndrome, possibly type-II, although the lack of the rest of the spinal column renders it impossible to verify other spinal anomalies. As a limitation, only the cranium and two cervical vertebrae were preserved, hence the possible involvement of the rest of the skeleton cannot be verified.